Faktor yang Mempengaruhi Nilai Perusahaan pada Perusahaan Sektor Property & Real Estate yang Terdaftar di Bursa Efek - Aang Syahdina; Anjela Puspita; Dhevia Pragatti; Lisnawati Lisnawati; Romanus Ama Raya Wai (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The purpose of this research is to test in reality whether profitability, leverage, and company size affect company value in real estate and property companies listed on the Indonesia Stock Exchange during the 2019-2023 period. This study uses secondary data, there are 10 companies that meet the research criteria many as 50 observation data. This study uses a quantitative method. The research variables used are profitability, leverage, and company size. This test uses multiple linear analysis and the eviews 13 software program. These results illustrate that profitability and leverage do not affect company value, while company size has a negative effect. according to the results of the regression test using (REM), the Determination Coefficient R² = 0.493716, indicating that 49.37% of company value is influenced by (ROAS), (DERA), and (UP), while the remaining 50.63% is explained by other factors.